Stand-alone water treatment: performance of electrospun nanofibers - Mataram, A. (Penerbit UTM Press, 2016)
The aim of this study was to evaluate the use of nanofiber microfiltration membranes, spun by an innovative electrospinning technique, in water filtration applications. This study bridges between developments in electrospinning techniques for the production of flat sheet membranes and the application of these membranes in water filtration. The functionalized or non-functionalized for the removal of pathogens was investigated, in term of chemical oxygen demand, total suspend solid and ammonium in the waste water. Physical properties such as clean water permeability (CWP) and strength were also examined. The results showed a very good removal of TSS (range 94.83-97.34%), COD (89.32-95.27%) and NH3-N (64.48-72.87%). These test showed that the electrospun membranes can be used for water filtration applications.